A Conceptual Framework for the Individual Factors Fostering the Innovative Work Behaviour of STEM Teachers - Daud, Siti Rohana; Rahim, Azira; Abdullah, Muhammad Syukri; Sehat, Nani Shuhada; Sarkam, Saida Farhanah; Abas, Norlela; Suhaime, Intan Liana (Information Management and Business Review, 2024)
This article explores the factors influencing innovative work behavior (IWB) among academics in the field of education, with a specific focus on STEM teachers. The inquiry adopts the conceptual framework of self-determination theory. A literature review methodology is employed, encompassing an examination of journals, conference papers, theses, and a conceptual approach. Variables in this analysis are delineated and measured in accordance with previous research and recommendations. The findings of this study highlight the significance of intrinsic motivation, self-efficacy, and job engagement as pivotal characteristics contributing to the cultivation of innovative work behavior among employees. The study’s limitations stem from its reliance on a literature review and the analysis of prior research findings to construct a conceptual framework concerning STEM teachers’ innovative work behavior. Future empirical research is recommended to comprehensively elucidate additional factors fostering innovative work behavior. The research findings corroborate earlier studies, suggesting that to bolster Malaysia’s standing in the Global Innovation Index (GII) and, indirectly, to advance the goals of the NSTIP 2021-2030 aimed at cultivating a technologically proficient society, educational administrators in Malaysia should actively foster teachers’ engagement in innovative work behavior activities, leveraging their competencies and strengths. This study provides valuable insights into the individual factors influencing teachers’ propensity for innovative work behavior and their potential to enhance Malaysia’s education system.